Entrepreneurship for social change - Sergi, Bruno S.; Scanlon, Cole C.; Heine, Luke R. I. (Lab for entrepreneurship and development., 2021)
Social entrepreneurship is revolutionizing the way societal challenges are being approached and solved. Instead of waiting for government or big business to take action, individuals across the world are developing and implementing innovative, effective, and sustainable solutions to some of our most pressing social and environmental challenges. In Entrepreneurship for Social Change, a cast of expert contributors explore how the growing trend towards social entrepreneurship, along with a variety of political, cultural and social influences, have developed across sectors and countries. The book features a diverse array of chapters on subjects such as peer-to-peer lending, venture capital, the digital silk road, small business contracting and women's health social enterprises.